if someone can solve this i will give brainliest
![if someone can solve this i will give brainliest class=](https://us-static.z-dn.net/files/dfc/8e1f3524687f8c414ae856b912d0f2b0.png)
Answer:
f(-7)= -21
f(13)= 99
Step-by-step explanation:
Find f(-7) and f(13) using this equation f(x)=3(2x+7).
To find f(-7) plug in -7 into all the x values in the equation.
f(-7)=3(2(-7)+7)
Multiply 2 and -7.
f(-7)=3(-14+7)
Add -14 and 7.
f(-7)=3(-7)=-21
For f(13) plug in 13 to all the x values.
f(13)=3(2(13)+7)
Multiply 2 and 13.
f(13)=3(26+7)
Add 26 and 7.
f(13)=3(33)=99
Hope this helps!
If not, I am sorry.